Substantive Religiosity among Adolescents: A Comparison between Junior High School and Madrasah Tsanawiyah in Bandung - Tya Shofarina M. Nur; Aceng Kosasih; Saepul Anwar; Nur Fatimah (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2025)
The decline of substantive religiosity among adolescents is an important issue in religious education, considering its impact on character formation and morality. This study aims to analyze and compare the level of substantive religiosity across four types of secondary schools in Bandung: State Junior High School, Private Junior High School, State Tsanawiyah Madrasah, and Private Tsanawiyah Madrasah. Data were analyzed using the one-way ANOVA test and the Tukey HSD post hoc test. The results showed significant differences in substantive religiosity between types of schools, F(3,438)=10.04, p = 0,001. Post hoc tests confirmed that Private Tsanawiyah Madrasah students showed significantly higher substantive religiosity than students in other schools. The biggest difference is seen in the ritualistic dimension, followed by the consequential dimension, while the ideological dimension shows minimal differences between schools. Although the structure and type of school influence substantive religiosity, particularly ritual practices, the gap between knowledge and behavior remains small in all schools. This indicates that external factors, such as family support, peer influence, and social media, are significant in shaping religious values into actual behaviors. This research emphasizes the importance of a holistic and collaborative approach involving family, peers, and community in developing substantive religiosity in adolescents.